1996
DOI: 10.1507/endocrj.43.suppl_s65
|View full text |Cite
|
Sign up to set email alerts
|

Signalling Pathway of GH.

Abstract: Abstract. GH has long been known as a regulator of body growth and metabolism, yet its mechanism of action at the cellular level has been elusive. We have recently shown that GH promotes the rapid association of GH receptor with the tyrosine kinase JAK2, activates JAK2, and promotes the tyrosyl phosphorylation of both JAK2 and GH receptor. This suggests that the initial signalling event in GH action is the activation of JAK2 which in turn phosphorylates tyrosines within JAK2 and GH receptor. We have identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
2

Year Published

1998
1998
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 32 publications
2
18
0
2
Order By: Relevance
“…We show that Jak2 is the kinase that phosphorylates Fpn in response to hepcidin, thereby identifying the molecular basis of Fpn down-regulation. The binding and activation of Jak2 to cytokine and growth factor receptors following ligand administration is well recognized (11,17). Fpn differs from cytokine and growth factor receptors as it is a polytopic membrane protein and not a single transmembrane protein.…”
Section: Discussionmentioning
confidence: 99%
“…We show that Jak2 is the kinase that phosphorylates Fpn in response to hepcidin, thereby identifying the molecular basis of Fpn down-regulation. The binding and activation of Jak2 to cytokine and growth factor receptors following ligand administration is well recognized (11,17). Fpn differs from cytokine and growth factor receptors as it is a polytopic membrane protein and not a single transmembrane protein.…”
Section: Discussionmentioning
confidence: 99%
“…We examined whether the transcription response was mediated by Stat transcription factors, as Jak2 is known to activate Stat transcription factors (6,7,11). Stat3 was coimmunoprecipitated with Fpn in the presence but not in the absence of hepcidin (Figure 2A).…”
Section: Hepcidin Binding To Fpn Induces a Transcriptional Response mentioning
confidence: 99%
“…Studies have shown that activation of Jak2, by growth factor or cytokine receptors, results in receptor phosphorylation as well as the phosphorylation of Stats, which are transcriptional activators (6,7). Here we demonstrate that activation of Jak2, through binding of hepcidin to Fpn, results in Stat3-mediated transcriptional activation of a large number of genes.…”
Section: Introductionmentioning
confidence: 99%
“…Growth hormone (GH), a multifunctional hormone secreted from somatotrophs of the anterior pituitary, regulates overall body and cell growth, carbohydrate-proteinlipid metabolism, and water-electrolyte balance (10,34). Production and release of GH are controlled tightly but occasionally fall into imbalance; GH excess results in acromegaly and gigantism, whereas its deficiency in children results in impaired growth and short stature.…”
Section: Introductionmentioning
confidence: 99%